Microwave remote sensing of snow-covered sea ice - Borgeaud, M.; Kong, J. A.; Lin, F. C. (1986)
Snow and ice are modeled as random media characterized by different dielectric constants and correlation functions. In order to model the brine inclusions of sea ice, the random medium is assumed to be anisotropic. A three-layer model is used to simulate a snow-covered ice field with the top layer being snow, the middle layer being ice, and the bottom layer being sea water. The theoretical results are illustrated for thick first-year sea ice covered by dry snow, and for artificial, thin first-year sea ice covered by wet snow as measured in controlled model tank experiments. The radar backscattering cross sections are seen to increase with snow cover for snow-covered sea ice owing to large volume scattering effects of snow.